National geographic eyewitness to the 20th century - National Geographic Society (U.S.). Book Division (Washington, D.C. : National Geographic Society, 2004)
A decade-by-decade examination of the primary themes and monumental events of the twentieth century, highlighted by six hundred photographs and illustrations.
Includes index.
Young Adult.
Young Adult
Keywords: History, Modern -- 20th century; History, Modern -- 20th century -- Chronology; Twentieth century; World history -- 20th century; World history -- 20th century; World history -- 20th century -- Chronology